Functional identification of the zebrafish Interleukin-1 receptor in an embryonic model of Il-1β-induced systemic inflammation - Sebo, Dylan J.; Fetsko, Audrey R.; Phipps, Kallie K.; Taylor, Michael R. (Frontiers in Immunology, 2022)
Interleukin-1β (IL-1β) is a potent proinflammatory cytokine that plays a vital role in the innate immune system. To observe the innate immune response in vivo, several transgenic zebrafish lines have been developed to model IL-1β-induced inflammation and to visualize immune cell migration and proliferation in real time. However, our understanding of the IL-1β response in zebrafish is limited due to an incomplete genome annotation and a lack of functional data for the cytokine receptors involved in the inflammatory process. Here, we use a combination of database mining, genetic analyses, and functional assays to identify zebrafish Interleukin-1 receptor, type 1 (Il1r1). We identified putative zebrafish il1r1 candidate genes that encode proteins with predicted structures similar to human IL1R1. To examine functionality of these candidates, we designed highly effective morpholinos to disrupt gene expression in a zebrafish model of embryonic Il-1β-induced systemic inflammation. In this double transgenic model, ubb:Gal4-EcR, uas:il1βmat, the zebrafish ubiquitin b (ubb) promoter drives expression of the modified Gal4 transcription factor fused to the ecdysone receptor (EcR), which in turn drives the tightly-regulated expression and secretion of mature Il-1β only in the presence of the ecdysone analog tebufenozide (Teb). Application of Teb to ubb:Gal4-EcR, uas:il1βmat embryos causes premature death, fin degradation, substantial neutrophil expansion, and generation of reactive oxygen species (ROS). To rescue these deleterious phenotypes, we injected ubb:Gal4-EcR, uas:il1βmat embryos with putative il1r1 morpholinos and found that knockdown of only one candidate gene prevented the adverse effects caused by Il-1β. Mosaic knockout of il1r1 using the CRISPR/Cas9 system phenocopied these results. Taken together, our study identifies the functional zebrafish Il1r1 utilizing a genetic model of Il-1β-induced inflammation and provides valuable new insights to study inflammatory conditions specifically driven by Il-1β or related to Il1r1 function in zebrafish.